PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anak Agung Ketut Trisnayanti; Ni Putu Yuria Mendra; Desak AYu Sriary Bhegawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The purpose of this study is to examine the Effects of Cash Turnover, Inventory Turnover, Receivable Turnover on Liquidity of Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange. The population in this study were all Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2018. Determination of the sample using purposive sampling method. The data analysis technique used in this study was multiple regression analysis. The results of testing the hypothesis using the statistical test t which shows that the cash turnover variable had a positive effect on liquidity, inventory turnover variable has a positive effect on liquidity and variable accounts receivable turnover does not affect liquidity.